1991
DOI: 10.1111/j.1460-9568.1991.tb00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Learning and Abnormal Open‐field Behaviours of Rats After Early Postnatal Anoxia and the Beneficial Effect of the Calcium Antagonist Nimodipine

Abstract: Perinatal anoxia/hypoxia is considered a serious risk factor for normal brain development. Anoxia induced by repeated asphyxia at 2 and 4 days after birth resulted in a transient hyperactivity in the small open-field, and a behavioural depression in adult open-field activity of male Wistar rats. The same treatment impaired adult learning behaviour in pole-jumping conditioned avoidance and appetitively motivated hole-board test situations. The calcium entry blocker nimodipine (in doses of 3 and 10 mg/kg) preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 37 publications
2
15
0
1
Order By: Relevance
“…These functional deficits were associated with decreased staining for neurofilament immunoreactivity, astrocytes (GFAP), and oligodendrocytes (RIP) in the hippocampus and somatosensory and motor cortices in the younger animals and only minimal changes in these regions upon reaching adulthood (30). Similar findings have been reported using other hypoxic paradigms during early postnatal life (31)(32)(33). For example, Nyakas and colleagues (34) have conclusively demonstrated that application of hypoxia or hypoxic-like treatments leads to substantial effects in the architectural development of specific neural regions (e.g.…”
Section: Discussionsupporting
confidence: 73%
“…These functional deficits were associated with decreased staining for neurofilament immunoreactivity, astrocytes (GFAP), and oligodendrocytes (RIP) in the hippocampus and somatosensory and motor cortices in the younger animals and only minimal changes in these regions upon reaching adulthood (30). Similar findings have been reported using other hypoxic paradigms during early postnatal life (31)(32)(33). For example, Nyakas and colleagues (34) have conclusively demonstrated that application of hypoxia or hypoxic-like treatments leads to substantial effects in the architectural development of specific neural regions (e.g.…”
Section: Discussionsupporting
confidence: 73%
“…These results are in accordance with previous data showing the ability of nimodipine to improve learning in either aged or hypertensive animals. [12][13][14][15][16][17][18][19] Notwithstanding, the present data from middle-aged normotensive WKY and SHR may further suggest that the presence of aging and hypertension produces additive cognitive alterations 2 that can be partially reversed by nimodipine. …”
Section: )mentioning
confidence: 88%
“…Because nimodipine was not altered by exposure to the body temperature during 4 weeks, 3 the behavioral and cardiovascular changes observed in the present study are due to drug treatment. With use of the multiple variable interval extinction test in 3-month-old SHR, but not in WKY of the same age, an improving effect of nimodipine on learning was detected 18,19 ; this lack of effect in WKY could have been due to the age of the animals (3 months). In fact, we found that 3-month-old but not middleaged (12-month-old) WKY display full ability to learn.…”
Section: Nimodipine Reverses Cognitive Deficitsmentioning
confidence: 92%
See 1 more Smart Citation
“…Seventy-two hours postsurgery, the behavior of the animals was assessed in a light-independent small open-field paradigm (Nyakas et al, 1991). Animals were placed into individual Perspex arenas, 24 ϫ 24 cm in diameter with 30-cm high transparent walls, for 25 min.…”
Section: Behavioral Testingmentioning
confidence: 99%